Failure of a gently inclined fractured rock slope induced by coal seam mining and its impact on transmission towers - Wu, Yu; Zhou, Lin; Li, Yi; Wu, Jianrong; Nie, Xianglun; Zhao, Donglei; Liu, Dandan (Frontiers in Earth Science, 2025)
The mechanisms by which continuous underground coal mining induces surface subsidence and adversely affects transmission towers within the region remain incompletely understood. This study takes the Wenjiaba mining area in Zhijin County, Bijie City, Guizhou Province, China, as a case study to elucidate these mechanisms. The research integrates field forensic investigations, laboratory-scale physical modeling, and two-dimensional discrete element numerical simulations. The study revealed that coal mining induces progressive failure of the overlying strata, with primary joints serving as the dominant pathways for fracture propagation. When the coal face advances to 150 m, the goaf roof collapses in a simply supported beam failure mode. By the time the coal face reaches 200 m, fractures have extended to the surface. As mining continues, the fractal dimension of cracks in the slope model progressively increases, with rock mass failure primarily governed by the activation of primary joints and bedding planes. Surface subsidence is identified as the key factor driving the differential settlement of transmission tower foundations. The 2D DEM simulation results further reveal that transmission tower 1, located at the edge of the mined-out area, has a tilt of approximately 0.55%, whereas transmission tower 2, situated at the center, exhibits a foundation tilt exceeding 2.2% due to greater subsidence. This study provides scientific support for risk assessment of power transmission infrastructure in coal mining regions of southwestern China.